Maqasid Sharia Jasser Auda Theory: Systems Approach to Islamic Family Law in the Digital Era - Musarrofa, Ita; Muttaqin, Husnul (Alhurriyah, 2024)
The digital era is characterized by the rapid use of information technology in daily human interactions. The telepresence feature of the virtual world, which allows for remote interactions, presents unique challenges for Islamic family law, which in some provisions requires the physical presence of parties when conducting contracts. Problems that arise include issues such as the validity of online marriage contracts (ijab kabul), fulfilling sexual needs of long-distance relationship (LDR) couples online, divorce and reconciliation via social media, and so forth. This paper aims to examine Jasser Auda's thoughts on maqasid Sharia using a systems approach by conducting a content analysis of Jasser Auda's main works in the field of maqasid Sharia. Jasser Auda's proposal is then tested for its ability to address the issues of family law in the virtual world. The six system features offered by Jasser Auda as a problem-solving method are highly relevant in providing solutions to the emerging issues of Islamic family law in the digital era. The features of openness and purposiveness provide ample room for society to freely leverage the potential of the digital world without losing authenticity to the primary Islamic texts. These features allow for the incorporation of digital customs (`urf) as a category of `urf that can serve as a legal basis in determining the rulings for various activities occurring in the virtual world.